Targeted Sonodynamic Therapy Platform for Holistic Integrative Helicobacter pylori Therapy - Xiaojing Yin; Yongkang Lai; Xinyuan Zhang; Tingling Zhang; Jing Tian; Yiqi Du; Zhaoshen Li; Jie Gao (Advanced Science)
Abstract Helicobacter pylori (H. pylori) is a primary pathogen associated with gastrointestinal diseases, including gastric cancer. The increase in resistance to antibiotics, along with the adverse effects caused by complicated medication protocols, has made the eradication of H. pylori a more formidable challenge, necessitating alternative therapeutics. Herein, a targeted nanoplatform is reported based on sonodynamic therapy, the chitosan‐conjugated fucose loaded with indocyanine green (ICG@FCS). It penetrates the gastric mucosa and homes in on H. pylori through dual targeting mechanisms: molecular via fucose and physical via ultrasound. Upon ultrasound activation, it generates singlet oxygen, effectively attacking planktonic bacteria, disrupting biofilms, and facilitating the clearance of intracellular bacteria by promoting autophagy, including multidrug‐resistant strains. The ICG@FCS nanoplatform minimally affects the gut microbiota and aids in gastric mucosa repair. a holistic integrative H. pylori therapy strategy is proposed that targets eradication while preserving gastrointestinal health. This strategy emphasizes the importance of maintaining patient health while eradicating the pathogen. This advancement is set to refine the comprehensive antibacterial approach, offering a promising horizon in the ongoing battle against antibiotic resistance and more effective gastric cancer prevention strategies.